Desempenho das exportações goianas do complexo soja para os principais parceiros comerciais: uma aplicação do modelo gravitacional - Silva, Frederico Teodoro da (2023)
The aim of this study was to analyze the performance of soy complex exports from the state of Goiás to the main importing countries - China, Netherlands, Thailand, France, South Korea, Spain, Germany and Iran - through the Gravity Model. The chosen period was from 2003 to 2019 and the destinations were selected because they had complete statistical information and because they represented approximately 88% of the Soy Complex exported by the state of Goiás. The Gravity Model was estimated in the formats Pooled, Fixed Effect and Random Effect, being the routines carried out in the R-4.1.2 software, taking into account the GDP of Goiás, the GDP of the importing country, the distance between the capitals, the price of soybeans and a binary variable that captures if China has a greater force in exports. According to the results of the three models, the export elasticity of the Soy Complex in relation to the GDP of Goiás is approximately 1.1% in the Pooled model, 0.64% in the Random Effect model. On the other hand, the export elasticity of the Soy Complex in relation to the GDP of the importing country is 1.81% in both the Fixed Effect model and the Random Effect model. The distance between the capitals was also a significant factor in the exports of the soy complex from Goiás. Furthermore, the results showed that China had a significantly greater influence on the soy complex exports from Goiás compared to the other importing countries. Therefore, the study concluded that it is vital to emphasize the strong dependence of Soy Complex exports from Goiás on China and the need to expand the diversification of these export destinations, in order to make them more diverse and less vulnerable to economic and political events restricted to a single country.